STUDY OF EFFECT SOME VEGETABLE OILS AND TWO TYPE OF FUNGI AGAINST THE VARROA (Academicia Globe: Inderscience Research, 2023)
This study included evaluating the effectiveness of some vegetable oils ( Pimpinella anisum oil , Nigella sativa , Syzygium aromaticum ) and Verticillium lacinii, Metarhizum anisopliae fungi in control on varroa after 24 and 48 hours of use , by placing oil-saturated paper at the bottom of the cells to find out which type of extracts are most effective in control, The study indicator that Metarhizum anisopliae is the most effective, reaching (85.98%), followed by Verticillium lacinii by (80.16)%, followed by Pimpinella anisum (78.3%), Syzygium aromaticum (% (73.1) and Nigella sativa (60.16%.